Social Network Strategy improves access to HIV testing and harm reduction programs for PWID and their partners in Kazakhstan - Denisiuk, Olga; Pavlo, Smyrnov; Batyrbekova, Ainura; Dudnik, Roman; Denebayeva, Alfiya; Zhandybayeva, Ainur; Kuznetsova, Yuliya; Tetyana, Deshko (The Journal of Infection in Developing Countries, 2023)
Introduction: The region of Eastern Europe and Сentral Asia has a growing HIV epidemic. Kazakhstan is a country in Central Asia with an estimated 33,000 people living with HIV. The new HIV infections have increased by 29% since 2010. Evidence suggests that HIV testing strategies focused on social networks are effective methods to identify more people with undiagnosed HIV. We conducted a study to describe the optimized HIV case finding (OCF) intervention for people who inject drugs (PWID) and their partners in Kazakhstan. Methodology: The OCF is based on recruitment of the extended risk social networks of HIV-positive PWID, using a two-step recruitment algorithm. Results: There were 5,983 PWIDs and their partners tested for HIV, of those 149 (2.5%) received HIV-positive test results and the majority 145 (97%) were newly identified HIV-positive. The characteristics which had a statistically significant positive association with HIV-positive test results included: age group 15-19 (OR 4.12, 95% CI 1.44-11.7); age group 20-24 (OR 1.97, 95% CI 1.03-3.8); age group 50+ (OR 2.45, 95% CI 1.48-4.1); male sex (OR 1.78; 95% CI 1.2-2.6), participants who have previously received harm reduction services (OR 1.48; 95% CI 1.0-2.2); partners from “other groups” (OR 2.31, 95% CI 1.3-4.2). Conclusions: Low-threshold HIV testing and harm reduction services, like OCF using directly assisted self-testing and social network strategies are essential in reaching key populations with HIV prevention, increasing access to HIV testing and care.